PENINGKATAN KETERAMPILAN BERPIKIR KREATIF SISWA KELAS III MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) - Saenal R; Daroe Iswatiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the creative thinking skills of third-grade students at MI Muhammadiyah Romang Lompoa by implementing the Problem Based Learning (PBL) model. Creative thinking is one of the essential 21st-century skills that students need to develop early, especially in elementary education. However, preliminary observations indicated that students struggled to generate ideas, solve problems independently, and express original thoughts in class activities. To address this issue, a Classroom Action Research (CAR) was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants of the study were 20 third-grade students. Data were collected through observation, creative thinking skill tests, and documentation. The results showed a significant improvement in students' creative thinking skills after applying the PBL model. All four indicators—fluency, flexibility, elaboration, and originality—showed noticeable progress from the first to the second cycle. These findings suggest that the PBL model is effective in fostering students’ creative thinking by engaging them in real-world problem-solving, collaborative discussions, and independent exploration. Therefore, the PBL approach can be recommended as a practical and impactful teaching strategy for elementary classrooms. Keywords: creative thinking, Problem Based Learning, classroom action research